PEMIKIRAN JAMAL AL-BANNA TENTANG RELASI SUAMI ISTERI DALAM KITAB AL-MAR’AH AL-MUSLIMAH BAINA TAHRĪR AL-QUR’ȂN WA TAQYĪD AL-FUQAHȂ - Faiz, Muhammad Fauzinuddin (Al-Mazaahib: Jurnal Perbandingan Hukum, 2015)
In the life of the Muslim community, the relationship between men and women, or, more specifically between husband and wife, are often not equal nor fair. Women are often considered more inferior, subordinate, and even considered a second-class human beings. The issue of gender injustice that encourages Jamal al-Banna to apply concepts or new ideas about the relationship between men and women (husband and wife) were more fair and equal. In order to achieve this goal, the relationship of husband and wife, according to Jamal al-Banna, should be based on principles of justice, equality (al-Musawah), propriety (al-ma'ruf), the collective agreement, as well as a sense of love and compassion incarnate in the form of speech and daily attitude. With these principles then Jamal al-Banna holds that in a family is not unconditional leadership of the husband, and also the lack of authority for a husband to beat his wife. In addition, he also called for a written marriage contract in order to protect the rights of each husband and wife, as well as appeals for wives career. This paper is going to study the Jamal al-Banna thought, especially with respect to the pattern of the relationship of husband and wife as set forth in the Book Mar'ah al-Tahrir al-Muslimah Baina Taqyīd the Qur'an wa al-jurists ". This paper is expected to enrich the wealth of knowledge of Islam and also able to drive to realize the family relationship more harmonious, fair and equitable gender.